Instruments for patient-reported outcomes and predictors in German rehabilitation research -- current developments within the 'Rehabilitation Sciences' Research Funding Programme. - Zwingmann C; Moock J; Kohlmann T (Rehabilitation, 2005)
In 1998, the German Federal Ministry of Education and Research (BMBF) and the German pension insurance scheme established a funding programme for research in rehabilitation. This initiative led to the establishment of eight regional research networks in which numerous research projects were sponsored for eight years (1998-2005). Within the framework of this funding programme, various self-assessment instruments were developed, adapted or improved in order to measure patient-reported outcomes and predictors. In sum, the analyses meet high psychometric standards. In this paper, a comprehensive review is given in five important assessment fields of rehabilitation research in Germany: Health-related quality of life (generic, disease-specific, children and adolescents, preference-based), evaluation of specific therapy and education programmes, motivation, screening for vocational problems and screening for comorbid mental disorders. The instruments are critically discussed, and perspectives for further research are pointed out.